Don’t put all your eggs in foreign baskets - Camara, Santiago (2020)
I analyze the sluggish response of exports during and after financial crises using firm level data for two countries-episodes: Argentina 2001 and Peru 1998 crises. I find that both incumbent exporting firms do not expand and that there’s no significant entry of new exporting firms. Furthermore, I present evidence that suggests that the export elasticity to the real exchange rate is asymmetric, smaller for depreciations than for appreciations. I build and estimate a DSGE model for a small open economy where exporting entrepreneurs are subject to financial frictions and balance sheet effects in order to try and explain these stylized facts. Although these frictions decrease the response of exports to movements in the exchange rate, I use computational exercises to show that they are not enough to explain the empirical results.